Peningkatan Kemampuan Berpikir Kritis Siswa Menggunakan Model Reciprocal Teaching Berbasis Media Educative Game Terhadap Siswa Kelas V SD Kayuapu - Juliyanto, Disky Dwi; Masfuah, Siti; Hilyana, F. Shoufika (Universitas Muria Kudus, 2023)
This study aims to analyze the increase in science critical thinking skills of fifth grade students at SD Kayuapu before and after using the Reciprocal Teaching learning model based on educative game media. The research design uses a quantitative experiment, namely the Pre-Experimental Design with the One-Group Pretest-Posttest Design model. The data obtained through the written test method is a description test. The location of this research will be carried out in class V SD Kayuapu. The sample in this study was 20 grade V students using the saturated sample technique. The results of this study show that the percentage of the N-Gain value is 56%, which indicates a fairly effective increase. So, there is an increase in students' pretest and posttest scores before and after learning using the Reciprocal Teaching model based on educative game media on the critical thinking skills of fifth grade students at SD Kayuapu.